THEORETICAL AND PRACTICAL ASPECTS OF SUSPENDING THE PERIOD OF PROSECUTORIAL INSPECTION OVER THE EXECUTION OF LAWS AND APPEALING SUCH INSPECTIONS (International Conference on Economics, Finance, Banking and Management, 2025)
This article highlights the specific features of suspending the period for conducting prosecutorial inspections over the execution of laws and the peculiarities of appealing such inspections. It presents certain official statistical data regarding conducted prosecutorial inspections as well as the results of a sociological survey conducted within the framework of scientific research. The author engages in academic discussion with the views of several legal scholars and presents their own scientific and theoretical position in relation to these perspectives. The experience of several countries, including Kazakhstan, Turkmenistan, and Kyrgyzstan, is comparatively analyzed with national legislation, and a number of theoretical and practice-oriented proposals are put forward.